Quinoa : food politics and agrarian life in the Andean highlands - Seligmann, Linda J., 1954- (Interpretations of culture in the new millennium., 2023)
"Quinoa's new status as a superfood has altered the economic fortunes of Quechua farmers in the Andean highlands. Linda Seligmann journeys to the Huanoquite region of Peru to track the mixed blessings brought about by the surging worldwide popularity of the "exquisite grain." Focusing on how Indigenous communities have confronted globalization, Seligmann examines the influence of food politics, development initiatives, and agrarian history on present-day quinoa production among the Huanoquiteños. She also looks at the human stories behind the transformation, from the work of quinoa brokers to the ways Huanoquite's men and women navigate the shifts in place and power occurring in the home and their communities. Finally, Seligmann considers how the environmental consequences of mining may impact the Huanoquiteños' ability to farm quinoa and maintain their established way of life. The untold story behind the popular health food, Quinoa illuminates how Indigenous communities have engaged with the politics and policies surrounding their production of a once-traditional, now-global product"--